Dental age estimation in Malaysian adults based on volumetric analysis of pulp/tooth ratio using CBCT data / Muhammad Khan Asif - Muhammad Khan, Asif (2017)
Secondary dentine formation is one of the vital physiological age-related change that occurs in the permanent dentition throughout life. This physiological agerelated factor can be used for dental age estimation and identification of unknown deceased persons. Aims To investigate the strength of association between chronological age and pulp/tooth volume ratio among the Malaysian population and to find which amongst these 3 types (Maxillary right canines, maxillary left canines, maxillary right central incisors) of investigated monoradicular teeth had the highest strength of correlation. Materials and Methods Three hundred CBCT scanned data of 153 males and 147 females’ belonging to either Chinese or Malay ethnicity, stored in the Oral and Maxillofacial Imaging Division, Faculty of Dentistry University of Malaya were selected according to the quality, image acquiring parameters and age of the patients at the time of registration. The subjects were divided into 5 age groups (10 years interval each group), ranging from 16 to 65 years to ensure balanced sample distribution across the 5 groups. Subsequently 100 maxillary left canines, 100 maxillary right canines and 100 maxillary right central incisors having no pathology and fully developed roots were selected from the database of 300 CBCT scans. Hence, one tooth per CBCT scan was selected. Maxillary right and maxillary left canines were selected for the study in order to investigate if any significant difference in the strength of correlation occurred between two similar types of teeth belonging to different iv subjects. CBCT data was acquired using the i-CAT Cone Beam 3D Dental Imaging System (Imaging Sciences International, Hatfield, USA). The scans selected had exposure parameters of 120 KV, 18 mA and the scans were acquired using voxel size of 0.30 mm and scanning time of 20 sec. Volumetric analysis was performed with MIMICS software (Materialise NV, Belgium, version 16.0). Data was analysed using SPSS version 20. Results The Pearson correlation and regression analysis showed a significant inverse association between pulp/tooth volume ratio and chronological age for all the 3 types of investigated teeth (p<0.01). Results showed the highest coefficient of determination (R2) values for maxillary central incisor (R2=0.696) followed by maxillary right canine (R2=0.545) and maxillary left canine (R2=0.527). The strength of correlation for both male and female was found to be very good. Fisher Z test results showed no significant difference in the correlation coefficient values between genders for all the 3 types of investigated teeth and for the whole sample (Z critical 1.96 for p < .05). Fisher Z test indicated no significant difference in the correlation coefficient values between maxillary right and maxillary left canines (P=0.88), despite these teeth being selected from different individuals. Conclusion The present study reinforced that pulp/tooth volume ratio with age is a valuable indicator for dental age estimation for Malaysian population. Maxillary right central incisor has shown the highest coefficient of determination value among all 3 types of investigated teeth. Furthermore, the results have showed that this method of dental age estimation is indeed gender independent.